Cardiorespiratory characteristics and cholesterol responses to a single session of heavy leg press exercise - Pafili, Z.K.; Bogdanis, G.C.; M Maridaki (Journal of Sports Science and Medicine, 2010)
The effect of resistance exercise on blood lipids is not clear yet. The purpose of this study was to examine the cholesterol responses to a heavy resistance leg press exercise emphasizing on the eccentric movement 24 and 48 hours following exercise and to quantify the cardiorespiratory responses of the exercise bout in an attempt to clarify the exercise characteristics that may be responsible for the effects of heavy resistance exercise on blood lipids. Nine healthy, untrained male volunteers aged 27.2 ± 1.1 yrs (76.2 ± 2.5 kg, 1.79 ± 0.02 m) performed a session of heavy RE emphasizing on the eccentric movement consisting of eight sets of inclined leg presses at six repetition maximum with 3-min rest intervals. Venous blood samples were obtained at rest (control) and 24 and 48 hours following exercise. Average VO2 at rest was 4.0 ± 0.4 ml·min-1·kg-1, during exercise 19.6 ± 0.2 ml·min-1·kg-1 and during the 180 sec recovery period between sets 12.5 ± 0.2 ml·min-1·kg-1. RER values decreased with the progression of the exercise and were significantly lower during the last four sets compared with the first four sets of the exercise session. Resting heart rate was 67 ± 2 bpm, and maximum heart rate during exercise was 168 ± 1 bspm. Serum creatine kinase was significantly elevated on day 1 (1090 ± 272 U·L-1, p < 0.03) and peaked on day 2 (1230 ± 440 U·L-1 p < 0.01). Total cholesterol, HDL cholesterol and calculated LDL cholesterol concentration did not change significantly following with exercise. This protocol of heavy resistance exercise has no effect on TC or cholesterol sub-fraction concentration 24 and 48 hours following exercise which may be due to the low energy expenditure of the exercise and/or to the gender of the participants. © Journal of Sports Science and Medicine.